The Policy Strategy for Sustainable Capture Fisheries Development - Kusdiantoro Kusdiantoro; Achmad Fahrudin; Sugeng Hari Wisudo; Bambang Juanda (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
The sustainability of capture fisheries development in Indonesia faces various challenges, such as climate change, pollution, resource degradation, and pressure from fluctuating commodity prices.Furthermore, a policy breakthrough with proper strategy is needed in realizing sustainable capture fisheries development. This study aims to formulate the most appropriate policy from several existed alternative policies to achieve sustainable capture fisheries development. Primary and secondary data are used in this study. A prospective analysis (SMIC-Prob-Expert) approach is used to formulate priority policy scenarios for capture fisheries development in Indonesia. As results, the analysis brings about six main priority alternative policies, namely: (1) increasing utilization of fisheries resources (SDI), (2) increasing capture fisheries productivity, (3) increasing fishermen household income, (4) providing fisheries insurance/social security, (5) improving status utilization of SDI, and (6) increase in the value of capture fisheries non-tax state revenue (PNBP). The analysis shows that policy scenario 01 (111111) or by implementing all alternatives policy simultaneously is the best choice. If the policymakers are faced with options, then the policy scenario becomes the last option to be taken simultaneously is not to choose a policy of providing insurance/social security tofishermen; or in the in this case policy scenario 05 (111011).